2017
DOI: 10.21037/tgh.2017.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Single injection dual phase CBCT technique ameliorates results of trans-arterial chemoembolization for hepatocellular cancer

Abstract: Cone-beam CT (CBCT) application to the field of trans-arterial chemoembolization has been recently the focus of several researches. This imaging modality is performed with a rotation of the C-arm around the patient, without needs of patient repositioning. Datasets are immediately processed, obtaining volumetric CT-like images with the possibility of post-processing and reconstruction of images. Dual phase CBCT recently introduced in clinical practice consists in a first arterial acquisition followed by a delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…More recently, CBCT has gained a role in assisting TACE procedures [12,14], but all the existing reports in literature were focused on CBCT sensitivity (pooled sensitivity 90%[95%CI 82%-95%]); in case of diameter < 10 mm, sensitivity 94.5%) [30,31]. Moreover, some Authors reported the ability of CBCT, generally in arterial phase only, to detect occult hepatic lesions (ranging: 11.5-28.7%) [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, CBCT has gained a role in assisting TACE procedures [12,14], but all the existing reports in literature were focused on CBCT sensitivity (pooled sensitivity 90%[95%CI 82%-95%]); in case of diameter < 10 mm, sensitivity 94.5%) [30,31]. Moreover, some Authors reported the ability of CBCT, generally in arterial phase only, to detect occult hepatic lesions (ranging: 11.5-28.7%) [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CBCT can be performed before TACE procedure and using contrast media injection as multiphasic imaging. In particular, CBCT has gained attention as a helper tool for tumor detection, intraprocedural guidance and treatment assessment during TACE [10][11][12].…”
Section: Main Bodymentioning
confidence: 99%
“…Despite this, literature evidence on oncological response of b-TACE over standard non occluded TACE is controversial [3][4][5][6] In order to evaluate the adjunctive value of b-TACE we retrospectively evaluated the results of patients treated in our institution with b-TACE and compared them with an historical cohort treated with non-occluded DEM-TACE. b-TACE and DEM-TACE were performed by the same team under dual phase CBCT guidance i.e..: better tumor/feeders visualization) 15 , with rigorous standardization of the embolization procedure (sequential embolization with 100 and 200 microns particles 12 ), being the only technical variable the balloon micro-catheter employment. B-TACE had a trend for higher TTR after an initial complete response vs DEM-TACE at 1-year, con rmed also by the Coxregression analyses weighted for the presence of micro-balloon catheter and tumors' diameter.…”
Section: Discussionmentioning
confidence: 99%
“…This ability is not just for show, but yield to some major clinical implications: the visualization of an occult nodule identifies a subset of population experiencing fast tumour growth, having consequences on the number of adjunctive treatments controlling tumour growth (adjunctive RFA, or TACE procedures) and prioritization for transplantation [4]. Moreover, bi-phasic CBCT, with its unique ability to intra-procedural permit nodule characterization, could help in patients' reclassification and real-time TACE strategy modification [5].…”
Section: Dear Editormentioning
confidence: 99%